Motivasi dan Kinerja Peternak Kaitannya dengan Keberlanjutan Usaha Sapi Perah - Nurlina, Lilis; Alim, Syahirul; Faranita, Dhea; Mauludin, M. Ali; Sulistyati, Marina; Yunasaf, Unang (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to analyze the motivation and performance of dairy farmers and their relationship with the sustainability of the dairy farming business. The research was conducted at Putra Saluyu 1, which included a multi-purpose cooperative Tandangsari with a survey method. The sample used in this study consisted of 60 farmers selected through Simple Random Sampling. The study results showed that the motivation was classified as high (65.0%), and the performance was classified as high (70.0%). There was a significant correlation between motivation and business sustainability with a Spearman's rank correlation coefficient value (rS = 0.464). Moreover, a significant correlation exists between performance and business sustainability with Spearman's rank correlation coefficient value (rS = 0.462).